Stigma and level of familiarity with opioid maintenance treatment (OMT) among specialist physicians in Israel - Rozner Lihi; Delayahu Yael; Brill Silviu; Sason Anat; Weinstein Marsha; Shoshan Stacy; Schreiber Shaul; Adelson Miriam; Peles Einat (BMC, 2023)
Abstract Context Opioid use disorder (OUD) poses significant public health problems that have increased dramatically, resulting in high rates of morbidity and mortality. Objectives To minimize the risk of an opioid epidemic in Israel and be prepared, we evaluated physicians' objective knowledge, level of stigma, and approach to prescribing opioids, risk factors, and identification of patients with substance use disorder (SUD), as well as their knowledge about opioid maintenance treatment (OMT) for OUD. Methods Anonymous computerized questionnaires were distributed nationally to physicians by the Israel Medical Association. Knowledge, stigma, and approach were scored. Results Of only 249 responders, 58.6% prescribe opioids, 32.1% prescribe cannabis, and 18.5% daily encounter patients with SUD. Logistic regression found the high knowledge group had daily encounters with SUD (Odds Ratio (OR) = 3.5, 95% CI 1.7-7.1) and were familiar with OMT (OR = 10.1, 95% CI 3.5-29.0). The high stigma group was characterized by physicians who prescribe opioids (OR = 1.7, 95% CI 1.0-2.9), but who self-reported having limited knowledge regarding OMT (OR = 2, 95% CI 1.1-3.7). The high approach group was characterized by those who prescribe opioids (OR = 11.7, 95% CI 4.9-28), prescribe cannabis (OR = 2.1, 95% CI 1.0-4.3), self-report having limited knowledge regarding OMT (OR = 11.2, 95% CI 1.4-89) and self-report identifying SUD (OR = 32.5, 95% CI 4.1-260). Conclusion High stigma was most evident among physicians who prescribe opioids but, importantly, who had limited knowledge specifically regarding OMT. Gaps in knowledge and approach were observed. An educational intervention is highly recommended to reduce stigma and increase referrals of patients for OMT, the most effective treatment for opioid use disorder.